The Christian religious education and the Javanese tradition of theory and teaching method: Experiences from the Bible and Ki Hajar Dewantara - Rantung, Djoys Anneke (KURIOS, 2024)
This study examines the intersection between Christian religious education and Javanese educational traditions, focusing on the theories and teaching methods found in the Bible and the philosophy of Ki Hajar Dewantara. The research highlights how biblical figures such as Abraham, Moses, David, Solomon, Nehemiah, Jesus, and Paul embodied educational principles that align with Dewantara’s education philosophy. Both traditions emphasize holistic education, character formation, mentorship, and community-based learning. By drawing from both traditions, Christian religious education in Indonesia can integrate biblical teachings with local wisdom to create a more effective and contextually relevant learning system. This synthesis can strengthen character formation, intellectual growth, and spiritual development while fostering a deeper appreciation of cultural heritage. The study ultimately advocates for a dynamic, inclusive Christian education that respects biblical principles and indigenous educational philosophies.